A Study of the Factors underlying Consumers’ Attitudes toward Advertising in iQIYI and in Television. - WANG, QIN (2017)
Social network sites have been developing very fast these days in the world, such as Youtube, Facebook, Twitter. Social network advertising is a kind of online advertising, and it highly possibly reaches more consumers through social network platforms. The iQIYI is one of the most popular online advertising mediums in China, and it is similar to Youtube as an online video player. Television is the typicality of traditional advertising platform, and it has been playing an important role as an advertising platform in advertising industry. Meanwhile, consumers’ attitudes or belief usually influence their consuming behaviors. Therefore, it is necessary to clarify the factors underlying consumers’ attitude toward advertising in iQIYI and television. This article mainly focuses on people’s personal belief about advertising, and the main factors influencing consumers’ attitude toward advertising in iQIYI and in television. With regard to the attitude factors, it is concluded that in iQIYI, advertising ethics is the most important factor compared to other four factors such as economic effects of advertising, social effects of advertising, advertising entertainment and advertising regulation to influence consumers’ attitude toward iQIYI’s advertising; in television, economic effects of advertising have the greatest impact compared with social effects of advertising, advertising entertainment and advertising practice as factors influencing consumers’ attitude toward television advertising. Moreover, it proved that iQIYI is not a very reliable advertising platform in China. This may be of interest to the marketers or advertisers, especially useful for the comparison between traditional advertising platform and social network advertising platform.